Inactivation of Equine Arteritis Virus by Indolicidin Peptide - Metz, Germán Ernesto; Azcurra, Miriam Beatriz; de Souza, Guilherme Sastre; de Arruda Brasil, Maria Carolina Oliveira [UNESP]; Cilli, Eduardo Maffud [UNESP]; Lorenzón, Esteban Nicolás (Springer Nature, 2025)
Equine viral arteritis is an economically important contagious disease caused by equine arteritis virus (EAV). Our objective was to evaluate the antiviral activity of indolicidin and K-indolicidin peptides against EAV. We found that indolicidin, but not K-indolicidin, completely inhibits EAV. Furthermore, indolicidin did not affect sperm quality parameters, the primary source of EAV transmission. This is the first report showing the potential of indolicidin as a candidate for use as a therapeutic agent against EAV and an additive in equine semen extenders.
Keywords: Antiviral activity; Equine arteritis virus; Indolicidin